The primary stability of arthroscopic subscapularis tendon repair depends on the suture technique: a biomechanical evaluation of 4 different repair techniques - Nacov, Julia A.; Kammerlohr, Sandra; Staat, Manfred; Buess, Eduard; Leschinger, Tim; Wegmann, Kilian; Müller, Lars P.; Hackl, Michael (Orthopaedic journal of sports medicine, 2025)
Background: Numerous single- and double-row repair techniques with simple and modified stitches have been described for subscapularis tendon tears. - Purpose/Hypothesis: This study aimed to uniformly evaluate the influence of 4 different repair techniques on the biomechanical performance of fixation for full-thickness subscapularis tendon tears. It was hypothesized that (1) the 2 modified single-row repair techniques would require more cycles to result in 3- and 5-mm gap formation and have a higher load to failure after cyclic loading than the simple single-row repair technique and (2) the double-row repair technique would also require more cycles to result in 3- and 5-mm gap formation and have a significantly higher load to failure after cyclic loading compared to the simple single-row repair technique. - Study Design: Controlled laboratory study. - Methods: Full-thickness subscapularis tendon tears were created in 32 fresh-frozen cadaveric shoulders, and the tears were treated in 1 of 4 ways: (1) single-row repair with the mattress stitch, (2) single-row repair with the modified lasso-loop stitch, (3) single-row repair with the modified Mason-Allen stitch, or (4) double-row repair. After repair, specimens were progressively cyclically loaded to 200 N, and the number of cycles to obtain a 3- and 5-mm gap was recorded. After cyclic loading, the specimens were loaded to failure at 500 mm/min, and ultimate failure loads were measured. - Results: There were no significant differences between either of the modified single-row repair techniques and the simple single-row repair technique. Double-row repair withstood significantly more cycles until 3-mm (P < .001) and 5-mm (P = .004) gap formation and had a higher ultimate failure load (P = .015) compared to the simple single-row repair technique, and double-row repair withstood more cycles until 3-mm gap formation (P = .003) compared with single-row repair with the modified lasso-loop stitch. No significant differences were found between double-row repair and single-row repair with the modified Mason-Allen stitch. - Conclusion: Findings indicated that (1) there was no significant biomechanical advantage of the modified single-row repair techniques over the simple single-row repair technique and (2) while the double-row repair technique was biomechanically superior to the simple single-row repair technique, there was no significant difference between single-row repair with the modified Mason-Allen stitch and double-row repair. - Clinical Relevance: Considering that double-row repair might not be useful in some tears because of the risk of overtensioning, modified single-row repair techniques appear to be an adequate refixation alternative.
Erstmals veröffentlicht: 14. April 2025
Gesehen am 23.06.2025